2022
DOI: 10.1002/cpe.6804
|View full text |Cite
|
Sign up to set email alerts
|

DiPETrans: A framework for distributed parallel execution of transactions of blocks in blockchains

Abstract: Contemporary blockchain such as Bitcoin and Ethereum execute transactions serially by miners and validators and determine the Proof-of-Work (PoW). Such serial execution is unable to exploit modern multi-core resources efficiently, hence limiting the system throughput and increasing the transaction acceptance latency. The objective of this work is to increase the transaction throughput by introducing parallel transaction execution using a static analysis over the transaction dependencies. We propose the DiPETra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Under the existing parallel transaction execution solutions 25,26,27,28,29 which perform static analysis on contracts, if several transactions call the deposit() function in Listing 1, we will find that all these transactions need to be executed serially. The main reason why parallel execution cannot be performed is that the read-write set of each transaction contains writes to the three state variables: currentAmount, goalReached, and isClosed, as shown in Figure 1.…”
Section: Limitations Of Current Static Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the existing parallel transaction execution solutions 25,26,27,28,29 which perform static analysis on contracts, if several transactions call the deposit() function in Listing 1, we will find that all these transactions need to be executed serially. The main reason why parallel execution cannot be performed is that the read-write set of each transaction contains writes to the three state variables: currentAmount, goalReached, and isClosed, as shown in Figure 1.…”
Section: Limitations Of Current Static Analysis Methodsmentioning
confidence: 99%
“…A promising solution for parallel transaction execution is to perform static analysis, then improve the parallelism according to the analysis results. There are two ways of static analysis, one is to perform static analysis on transaction payload 27 , and another is to perform read-write static analysis on contract source code or bytecode. The grouping granularity of the former is coarse, and it can only be grouped according to the accounts and contracts involved in the transaction.…”
Section: Transaction Parallel Executionmentioning
confidence: 99%
See 1 more Smart Citation
“…As soluc ¸ões vistas até aqui utilizam paralelismo dentro dos peers através da utilizac ¸ão de arquiteturas multi-cores. Seguindo outra abordagem, Baheti et al [Baheti et al 2022] propuseram uma soluc ¸ão baseada em líder-seguidores que formam um comitê de peers. O líder analisa estaticamente as transac ¸ões, criando diferentes grupos (shards) de transac ¸ões independentes e as distribui aos seguidores para execuc ¸ão concorrente.…”
Section: Saraph E Herlihyunclassified
“…Another method called DiPETrans (Distributed Parallel Execution of Transactions) was introduced by Baheti et al (11) , which identified the transactions of blocks using the statistical analysis of shards. The mechanism, ever connected to the Blockchain server, enables the leader to perform the tasks of both segmenting blocks and the followers in handling the mining activities.…”
Section: Introductionmentioning
confidence: 99%